Tumor necrosis factor-alpha 308 G/A polymorphism and type 2 diabetes mellitus; a systematic review and meta-analysis - Ali Hasanpour Dehkordi; Majid Dousti; Faezeh Kiani; Mona Zamanian Azodi; Mostafa RezaeiTavirani; Kourosh Sayehmir (Journal of Nephropathology, 2018)
Context: Type 2 diabetes mellitus (T2DM) is a multi-factorial disease with several genetic and environmental factors known to be associated with the disease. Tumor necrosis factoralpha (TNF-α) acts on fat cells associated with increased insulin resistance and obesity and its increase can be associated with the prevalence of T2DM. Previous studies on the relationship between 308 G/A polymorphism in TNF-α and T2DM were not conclusive. The aim of this study was to investigate the association between 308 G/A polymorphism in TNF-α gene and T2DM using a systematic review and meta-analysis. Evidence Acquisitions: In this systematic review we searched all published studies about the association between TNF 308 G/A polymorphism and T2DM through databases such as Scopus, Science direct, PubMed and Google scholar. A fixed or random effect model was used on the basis of heterogeneity. The heterogeneity was assessed using the I2 index. We used STATA software (version 11.2) for data analysis. Results: In 22 selected papers, the total number of T2DM and control subject was 8485 and 8615, respectively. Odds ratios (ORs) with 95% confidence intervals(CI) for the GG genotype polymorphism 308 G/A in total, Asian populations and whites (Caucasian) were estimated as OR=0.98 (95% CI: 0.96-1.00), OR=0.96 (95% CI: 0.93 to 0.99) and OR=1.00 (95% CI: 0.97 to 1.40). The Publication Bias/or heterogeneity was observed in this study. Conclusions: The present investigation have shown that 308 G/A polymorphism GG and GA genotypes in TNF-α gene cannot be considered as predictors of T2DM (P<0.05).